"Congratulations, you're on TV!": Middle-space performances of live tweeters during the FIFA World Cup. (October 2018) - Salomaa, Elina; Lehtinen, Esa
Highlights: Live tweeting during the FIFA World Cup is analyzed with digital conversation analysis. Television publicity changes the direction of interaction between live tweeters. Publicity is appreciated through noticings, congratulations and compliments. Responses to these actions show a dilemma between agreeing and displaying modesty. Tweeting during the media event can be seen as a middle-space performance. Abstract: Social television has transformed the traditional role of the television viewers by providing 'ordinary people' access to the public stage. This article describes how public access to television affected the dialogues of Finnish tweeters on Twitter during the massive media event of the FIFA World Cup. Through the lens of digital conversation analysis, the study shows how the media publicity of tweets changed the direction of the interaction between tweeters and transformed their roles vis-à-vis the television show, making one of them into a 'media flasher' and the others viewers of his or her performance. The publicity was constructed as important through noticings, congratulations, and compliments, and in their responses to these actions the participants oriented to dilemmatic expectations of agreeing with the previous speaker and displaying modesty and authenticity. The activities of live tweeters can be seen as middle-space performances where ordinariness and celebrity are intertwined.